MODEL PERGERAKAN KOTA BANDAR LAMPUNG BERDASARKAN INTENSITAS GUNA LAHAN - Arif Ramadhan; Muhammad Zainal Ibad; Rahayu Sulistyorini (Jurnal Perencanaan dan Pengembangan Kebijakan, 2021)
The city functions as a service system for diverse community needs implemented through the provision of housing, trade and services, recreational areas and transportation networks. Activities between these activities cause movement, the magnitude of the movement value is influenced by the size and scale of activity (intensity) on each type of land use. The economic condition of the city depends on the ease of the people in their activities and the smooth distribution of production goods. Bandar Lampung as the economic center of Lampung Province has problems that affect movement such as land use patterns, low road accessibility. In anticipation of this movement must be in good condition that is effective and easy to do, because movement is influenced by land use intensity. Therefore, it is necessary to know the magnitude of the influence of the intensity of land use in the movement in the city of Bandar Lampung by using the Movement Model can be known the size of the influence of Land Intensity on the movement in the city of Bandar Lampung. The analytical method used in this study is the analysis of the origin destination matrix and multiple linear regression analysis. the results of the analysis show that land use related and influencing the movement of the city of Bandar Lampung are activities on land use trade and services as well as education affect movement. The resulting movement model is as follows: y = 62,3 + 2,275 + 1,348 .